A New Method Based on Multi Agent System and Artificial Immune System for Systematic Maintenance, ISSN/ISBN 2040-7459 /2040-7467 © Maxwell Scientific Organization, 2014 - Abdelhadi Adel; Mouss Leila Hayet (RJASET Research Journal of Applied Sciences, Engineering and Technology, 2014)
This study propose a novel method for the integration of systematic preventive maintenance policies in hybrid flow shop scheduling. The proposed approach is inspired by the behavior of the human body. We have implemented a problem-solving approach for optimizing the processing time, methods based on Métaheuristiques. This hybridization is between a Multi agent system and inspirations of the human body, especially artificial immune system. The effectiveness of our approach has been demonstrated repeatedly in this study. The proposed approach is applied to three preventive maintenance policies. These policies are intended to maximize the availability or to maintain a minimum level of reliability during the production chain. The results show that our algorithm outperforms existing algorithms. We assumed that the machines might be unavailable periodically during the production scheduling.